2009
DOI: 10.1038/ismej.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complex bacterial communities colonizing biliary stents reveals a host-dependent diversity

Abstract: This study provides a comprehensive survey of the spatial and temporal bacterial composition of biliary stent biofilms. The bacterial diversity, distribution and dynamics of 59 biliary and 4 pancreatic stent communities from 40 patients being treated at two different hospitals, which implant stents either simultaneously or consecutively, were characterized by single-strand conformation polymorphism (SSCP) analysis. Fifty-one phylotypes belonging to 5 bacterial phyla and 24 bacterial families were detected acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In contrast, for a subset of patients, we observed the emergence of a potential Escherichia-Shigella-dominated enterotype, and this was absent in four distinct cohorts of healthy individuals. We also observed a relationship among Escherichia-Shigella, Veillonella, and Streptococcus in the network analysis, which is in line with reports of the coaggregation of these bacterial groups in previous studies (6). Predictive metagenomics comparing the Escherichia-Shigella enterotype with other patients showed a striking enrichment of proinflammatory pathways, such as bacterial invasion of epithelial cells, lipopolysaccharide biosynthesis proteins, and the RIG-I-like receptor signaling pathway, as well as a decrease in beneficial bacterial functions, such as flavone and flavonol biosynthesis.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, for a subset of patients, we observed the emergence of a potential Escherichia-Shigella-dominated enterotype, and this was absent in four distinct cohorts of healthy individuals. We also observed a relationship among Escherichia-Shigella, Veillonella, and Streptococcus in the network analysis, which is in line with reports of the coaggregation of these bacterial groups in previous studies (6). Predictive metagenomics comparing the Escherichia-Shigella enterotype with other patients showed a striking enrichment of proinflammatory pathways, such as bacterial invasion of epithelial cells, lipopolysaccharide biosynthesis proteins, and the RIG-I-like receptor signaling pathway, as well as a decrease in beneficial bacterial functions, such as flavone and flavonol biosynthesis.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, it has been shown that the pancreatic duct or stents within the duct in the setting of chronic pancreatitis contain a rich biofilm containing bacteria 6,7 . The bile duct has also been considered to be generally sterile 6 but a number of studies have demonstrated the presence of bacteria in the biliary system in the setting of bile duct obstruction 6,8,9 . However, little is known about the presence of microbes within the pancreas or bile duct in the setting of cancer or how these microbes might affect treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These bands correspond to two species belonging to the phylum Firmicutes, being one of them related with the genus Streptococcus sp. (B3–B11),26 which have been found in waste digestion systems 27, 28. These species could be involved in the hydrolysis of the particulate matter of UIO wastewater.…”
Section: Resultsmentioning
confidence: 99%